Handheld 3D scanning as a minimally invasive measuring technique for neonatal anthropometry. (October 2019) - Andrews, Edward T.; Ashton, James J.; Pearson, Freya; Beattie, R. Mark; Johnson, Mark J.
Summary: Background: Measurement of length and head circumference (HC) in addition to weight is vital in assessing the nutritional status of preterm infants. Current anthropometry represents an interruption to preterm infants, and may not be possible in unstable infants. Handheld 3D scanning has the potential to perform bedside anthropometry (length and HC) in a less invasive manner. We aimed to evaluate the feasibility and performance of 3D scanning as a 'non-touch' measuring technique for routine anthropometry. Methods: Preterm infants born before 30 weeks gestation were recruited from a single neonatal unit. HC and length were measured both manually and by a handheld 3D scanner at recruitment and weekly until discharge. The two methods were compared using the Bland-Altman method and linear regression. Results: Seventeen infants had manual and 3D-scan measurements (67 HC, 87 length). The mean difference (95%CI) between manual and 3D-scan measures, as a percentage of the manual value, was 2.87% (2.27–3.47%) for HC and 3.10% (2.65–3.54%) for length. Correlation between manual and 3D measures was high; HC r = 0.957 and length 0.963. Bland-Altman plots showed reasonable agreement between the two methods, and there was a high correlation between scanner and manual measurements. Conclusions: These data show a high correlation between measurements gathered from 3D scan images and standard anthropometry. However, 3D measures are not yet precise enough for routine clinical use. Refinement of technique/technology may translate into practical monitoring the growth of preterm infants with minimal handling and without interruption to developmental care.